2011
DOI: 10.1159/000334425
|View full text |Cite
|
Sign up to set email alerts
|

Primary Squamous Cell Carcinoma of the Liver: An Uncommon Finding in Contrast-Enhanced Ultrasonography Imaging

Abstract: Primary squamous cell carcinoma (SCC) of the liver is rare tumor with an unfavorable prognosis. We report a case of advanced primary SCC of the liver arising adjacent to a nonparasitic liver cyst, invading into the right diaphragm and the right lung tissue. Contrast-enhanced ultrasonography (CE-US) demonstrated unique enhancement in the late vascular phase, which was incompatible with those observed in hepatocellular carcinoma, cholangiocellular carcinoma, or metastatic adenocarcinoma. The patient underwent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Besides the resection, previously reported methods included transcatheter arterial infusion chemotherapy (TACE), which was considered to be useful for both primary hepatic SCC and ASC patients [ 22 ]. Systemic chemotherapy was also reported in the therapeutic course of SCC and ASC [ 21 , 33 ]. Although these therapeutic methods were reported to have significant treatment effects, they usually were adopted just as adjuvant therapy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the resection, previously reported methods included transcatheter arterial infusion chemotherapy (TACE), which was considered to be useful for both primary hepatic SCC and ASC patients [ 22 ]. Systemic chemotherapy was also reported in the therapeutic course of SCC and ASC [ 21 , 33 ]. Although these therapeutic methods were reported to have significant treatment effects, they usually were adopted just as adjuvant therapy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like most of the hepatic malignancy, surgical resectability and operability is one of the most important factors deciding prognosis [ 8 ]. If surgical resection could be performed before tumor invading surrounding liver parenchyma, this could lead to a good prognosis [ 9 - 11 ]. Weimann et al performed surgical resection for primary SCC of the liver, without any adjuvant chemotherapy or radiation therapy, and patient survived more than 4 years [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Banbury et al also performed surgical resection for primary SCC of the liver, and patient survived more than 16 months without any adjuvant therapy [ 9 ]. But most of the cases of primary SCC of the liver are advanced, surgical resection alone cannot promise good prognosis and improve overall survival, and that radiation therapy or chemotherapy with 5-FU and/or CDDP should be considered with complete surgical resection [ 11 ]. Boscolo et al reported to have successfully treated advanced primary SCC of the liver with systemic CDDP and 5-FU therapy with surgical resection [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… 28 Chemotherapy, TACE, and even radiation could be used in these inoperable patients or as adjuvant treatments before and after surgery. 20 , 23 , 25 , 27 – 29…”
Section: Discussionmentioning
confidence: 99%
“… 1 27 The prognosis of this tumor is extremely poor, only a few patients survived more than 12 months even after treatment as reported. 10 , 12 , 23 26 , 28 30 Therefore, primary liver SCC is extremely rare occurred and different from other primary liver cancers.…”
Section: Introductionmentioning
confidence: 99%